PROVISION AND REJUVENATION OF LEARNING SUPPORT FACILITIES AT MTs BAITUL MUBAROK, KUBU RAYA REGENCY - Asmadi; Sarpawi; Rizal; Iwan Supardi; Helyanto; Rona Ariyansyah; Muhammad Taufik Habibillah Ibnu Ahmad; Rasiwan; Muhammad Abduh; Susi Hariyani (RADJA PUBLIKA, 2026)
The limited learning facilities at MTs Baitul Mubarok, including the absence of classroom ceilings, damaged doors, and unfit desks, chairs, and whiteboards, have hindered comfort and safety in the learning process. The Community Service Program (PKM) of the Civil Engineering Department at Politeknik Negeri Pontianak was carried out to provide and refurbish these facilities while offering practical learning experiences for students. The method included situation analysis, planning, material preparation, product fabrication in the workshop, and delivery to the partner. The program produced 36 desks, 76 chairs, 3 whiteboards, and 3 sets of classroom doors, all meeting the standards of Permendiknas No. 24/2007. The activity improved the quality of learning facilities, enhanced student comfort, and strengthened students' technical skills and social awareness, although ceiling repairs could not be completed due to budget limitations.